Extrinsic and intrinsic factors influencing the emergence and return of the Asian particolored bat Vespertilio sinensis to the summer roost. Issue 5 (13th May 2022) - Feng, Lei; Qin, Hexuan; Li, Jingjing; Li, Xin; Feng, Jiang; Jiang, Tinglei
Abstract: Circadian rhythms play a crucial role in the health and survival of organisms. However, little is known concerning how intrinsic and extrinsic factors affect animal daily rhythms in the field, especially in nocturnal animals. Here, we investigated the first emergence, mid‐emergence, and return times of Vespertilio sinensis, and also integrated environmental conditions (temperature, humidity, and light intensity) and biotic factors (reproductive status and predation risk) to determine causes of variation in the activity rhythms of the bats. We found that variation in the first emergence time, the mid‐emergence time, and the final return time were distinct. The results demonstrated that the emergence and return times of bats were affected by light intensity, reproductive status, and predation risk in a relatively complex pattern. Light intensity had the greatest contribution to activity rhythms. Moreover, we first investigated the effects of actual predators on the activity rhythms of bats; the results showed that the mid‐emergence time of bats was earlier as predators were hunting, but the final return time was later when predators were present. Finally, our results also highlighted the importance of higher energy demands during the lactation in bats to variation in activity rhythms. These results improve our understanding of the patterns and causes of variation in activity rhythms in bats and other nocturnal animals. Abstract : Circadian rhythm is an adaptive life history characteristic of an organism. For example, human beings are active during the day and rest at night, which is the behavior manifestation of circadian rhythm. Animals' circadian rhythms are influenced by a variety of factors such as light, temperature and humidity, reproduction, and predators. So, we wanted to know what would affect the circadian rhythms of Asian particolored bats, which is a small bat species found in East Asia.